2017
DOI: 10.1002/acm2.12149
|View full text |Cite
|
Sign up to set email alerts
|

Clinical implementation and evaluation of the Acuros dose calculation algorithm

Abstract: PurposeThe main aim of this study is to validate the Acuros XB dose calculation algorithm for a Varian Clinac iX linac in our clinics, and subsequently compare it with the wildely used AAA algorithm.Methods and materialsThe source models for both Acuros XB and AAA were configured by importing the same measured beam data into Eclipse treatment planning system. Both algorithms were validated by comparing calculated dose with measured dose on a homogeneous water phantom for field sizes ranging from 6 cm × 6 cm to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(46 citation statements)
references
References 14 publications
1
45
0
Order By: Relevance
“…Based on the results, they concluded that AXB was more appropriate to use for dose calculations when low‐density heterogeneities were involved. Other studies 35–37 have drawn similar conclusions, that although both the AXB and the AAA algorithm can meet the RTOG 0813 dosimetric criteria, in general, AXB presented an improved dosimetric accuracy in the presence of inhomogeneity.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Based on the results, they concluded that AXB was more appropriate to use for dose calculations when low‐density heterogeneities were involved. Other studies 35–37 have drawn similar conclusions, that although both the AXB and the AAA algorithm can meet the RTOG 0813 dosimetric criteria, in general, AXB presented an improved dosimetric accuracy in the presence of inhomogeneity.…”
Section: Discussionmentioning
confidence: 55%
“…Based on the results, they concluded that AXB was more appropriate to use for dose calculations when low-density heterogeneities were involved. Other studies [35][36][37] have drawn similar conclusions, that although both the AXB and heterogeneous tissues or tissue interfaces, it was most likely due to differences in the algorithm. It can also be seen that the Halcyon AAA model tends to predict higher doses in the lung/tissue interface, which is consistent with previous literature.…”
Section: B | Advanced Tests For Specific Planning or Treatment Condmentioning
confidence: 69%
“…The dosimetric accuracy of LBTE has been investigated for a range of materials and treatment geometries and techniques [6][7][8][9], the findings generally indicating improved accuracy of the LBTE algorithm over Type B algorithms. The impact of reporting to D w and D m has been discussed for lung [10][11][12], breast [13], bone [14,15] and head and neck [16][17][18]. Recommendations have also been made for reporting dose in the routine clinical setting and in clinical trials [4,19] in the context of both Monte Carlo and LBTE algorithms.…”
Section: Introductionmentioning
confidence: 99%
“…In this work, the ArucosXB algorithm was used and the lung consolidation was considered to improve dose calculation accuracy inside lung. AcurosXB has been shown to be more accurate than the convolution-superposition type of algorithms, especially in the low density lung tissues and the lung soft tissue interface [16,17]. However, we realized that the determination of lung consolidation level from either chest X-ray or an OBI image may have large uncertainty.…”
Section: Discussionmentioning
confidence: 96%